Sleep Quality Relates to Metabolic Health in Second Trimester of Pregnancy. (14th June 2022) - Hand, Lauren; Hull, Holly; Siengsukon, Catherine; Herman, Amy
Abstract: Objectives: Examine the relationships between self-reported sleep quality parameters and markers of metabolic health during pregnancy. Methods: Baseline data collected at 12–20 weeks gestation from pregnant women enrolled in a high-fiber RCT (SPROUT; NCT04868110) were analyzed. Exclusion criteria included any known metabolic disturbance (e.g., history of diabetes, preeclampsia, hypertension). At the visit, a fasted blood draw, height, and weight were performed. Self-reported pre-pregnancy weight was collected. Sleep quality was assessed using the global Pittsburg Sleep Quality Index score (PSQI; >5 indicates poorer overall sleep quality) and sleep efficiency from the PSQI (100-point scale, higher indicates better efficiency). Total cholesterol (TC), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), triglycerides (TG), serum glucose, serum insulin, and hemoglobin A1c were analyzed using standardized protocols. Pearson's correlations, means, and standard deviations were performed. Results: Thirty-three participants were included in the analyses. Participants had a pre-pregnancy BMI of 25.4 ± 4.3 kg/m 2, PSQI of 4.61 ± 2.4, and sleep efficiency of 89.8 ± 10.7. Sleep efficiency was related to TC (r = −0.41, p = 0.018) and LDL-C (r = −0.418, p = 0.016); and PSQI was related to LDL-C (r = 0.372, p = 0.033). No relationships were found between sleep parameters and other lipid or glycemic markers. Conclusions: In a group of low-risk pregnant women, lower sleep efficiency and overall sleep quality were related to higher levels of blood lipids. Funding Sources: Internal funding received from School of Health Professions at presenting author's academic institution.